2018
DOI: 10.3389/fphar.2018.01124
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel General Medication Adherence Scale (GMAS) for Chronic Illness Patients in Pakistan

Abstract: Objective: This study aimed to develop and validate a self-reporting adherence tool termed as General Medication Adherence Scale (GMAS) in Urdu language for measuring adherence toward medication use among Pakistani patients with a chronic disease.Methods: A month-long study (December 2017) was conducted in three tertiary health care settings of Karachi, Pakistan. The tool underwent content and face validity as well as factor analyses, i.e., exploratory, partial confirmatory and confirmatory factor analyses. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 36 publications
7
94
0
1
Order By: Relevance
“…This was done with an item‐to‐respondent ratio of 1:15. Studies have recommended a ratio of 1:5 up to 1:20 . The explored factor structure was then confirmed using partial confirmatory factor analysis (PCFA) using maximum likelihood analysis with Varimax rotation.…”
Section: Methodsmentioning
confidence: 99%
“…This was done with an item‐to‐respondent ratio of 1:15. Studies have recommended a ratio of 1:5 up to 1:20 . The explored factor structure was then confirmed using partial confirmatory factor analysis (PCFA) using maximum likelihood analysis with Varimax rotation.…”
Section: Methodsmentioning
confidence: 99%
“…A novel scale termed as the General Medication Adherence Scale (GMAS) was originally formulated in Urdu language by Naqvi and colleagues that contained 11 items divided into three sections and was validated holistically in patients with chronic illnesses (Naqvi et al, 2018b;Naqvi and Hassali, 2019). However, psychometric properties of GMAS have not been validated in patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“…patient-, disease-, condition-, social/economic-and health systemrelated 1,2 ). In chronic disease, several studies have shown a relationship between adherence and patients' beliefs in medicines [5][6][7][8][9][10][11][12] . Higher adherence rates in chronic disease have also been equated with better patient experiences with current and past care 13,14 .…”
Section: Introductionmentioning
confidence: 99%